STRATEGI MARKETING POLITIK ANAK AGUNG KETUT SUJANA DALAM MEMENANGKAN PEMILU LEGISLATIF DPRD KOTA DENPASAR PERIODE 2019- 2024 (Jurnal Nawala Politika, 2022)
This research aims to find out how the political marketing strategy of Anak Agung Ketut Sujana in winning the Denpasar City Regional People's Representative Council Legislative Election for the 2019-2024 period. This research uses a qualitative approach with a case study method. Primary data are obtained from through interviews and documentation, both structured and unstructured. Meanwhile, secondary data was obtained through literature and literature studies and the internet related to this research. Based on the findings of the data obtained in this study, it can be concluded that the political marketing strategy of Anak Agung Ketut Sujana to win the second election in the 2019-2024 period is in the way as expressed in the 4P Political Marketing Theory, including: Product (Good political career and supported by major political parties), Promotion (Campaign with social society), Price (considerable capital or campaign funds), Place (The goal of a place to get a lot of votes), and and also social capital as an incumbent to garner as many votes as possible. With a track record, supported by major political parties, door to door campaigns, campaigns that prioritize social society, and have good social capital because they have served before so that Anak Agung Ketut Sujana can be re-elected as a member of the Denpasar City Regional People's Representative Council 2019 – 2024. Keywords: Political Marketing Strategy, Denpasar City Regional People's Representative Council, General Election.